Empowerment of Haranggaol Subdistrict community, Haranggaol Horison District, Simalungun Regency, North Sumatra in efforts to improve local wisdom - Ritonga, Fajar Utama; Siagian, Matias; Masmur, Indra (Talenta Publisher, 2019)
The Collaborative Work Lecture with BKS West PTN is one of the community service programs conducted by 20 state universities where the University of North Sumatra is the host of the program. In the KKN program, we realize one of the tri dharma of higher education namely community empowerment. The aim of this program is that students are expected to gain learning experience through involvement in the community who directly find, formulate, solve and overcome problems that are in the field. The Community Service Program that we carry out is devoted to the community in Haranggaol Village, Haraggaol Horison District, Simalungun Regency, North Sumatra Province with the program